(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2021)
Temporary ponds of Uruguay and the invertebrates that inhabit them represent relatively unexplored ecosystems, without clear references in relation to the diversity levels they host. In the present work we report the presence of 216 species and morphospecies of invertebrates and a total estimate of richness between 263 and 373 species, for 18 temporary ponds of Castillos Lagoon Basin, in the department of Rocha, Uruguay. This high species diversity would allow maintaining the stability of ecosystem functioning and the services it provides, such as drinking water, attenuation of hydrological pulses in lagoons and rivers, forage for livestock, limitation in the abundance of pathogens and disease outbreaks or system resistance against contaminants. Ecological studies in temporary ponds are excellent models for biodiversity studies and provide results that can be generalized to other ecosystems. However, one of the limitations raised in this work was the difficulty for the taxonomic identification of invertebrates. The management of diversity needs a solid taxonomic base that allows knowing the composition and structure of that diversity. Therefore, we highlight the importance of systematic studies of freshwater invertebrates in Uruguay.